Evaluasi Kondisi Fisik Dan Respons Fisiologis Atlet Tinju Provinsi Gorontalo - Haryani, Meri; Irawan, Safri; Duhe, Edy Dharma Putra; Nurkhoiroh; Haryanto, Arief Ibnu; Suardika, I Kadek (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This cross-sectional descriptive quantitative study aims to evaluate the physical condition and physiological responses of 15 PERTINA boxing athletes from Gorontalo Province (aged 17–23 years) ahead of the National Martial Arts Games (PON), using a total sampling technique. The physical test results showed an average of: 42.93 push-ups, 46.47 sit-ups, 54.47 cm vertical jump, 4.86 seconds 30-meter sprint, 11.24 seconds Illinois Agility Test, 32.07 cm flexibility, and VO₂Max 48.93 ml/kg/minute. Post-match simulation, physiological responses showed an increase in average pulse rate (71.73 to 163.13 beats/minute) and systolic blood pressure (117.33 to 138.27 mmHg). A Rating of Perceived Exertion (RPE) value of 16 indicates that the activity was perceived as strenuous by the athletes. In conclusion, the physical condition of Gorontalo Province's boxing athletes has supported their preparation for the National Martial Arts Games, but still requires intensive strengthening in terms of endurance, recovery, and tolerance for high-intensity activities.